Analysis of Factors Affecting User Satisfaction of E-Commerce Applications Using End-User Computing Satisfaction (EUCS) Method - Prabawanti, Ratih; Sihombing, Denny Jean Cross (Journal of Information Systems and Informatics, 2023)
The current era is marked by rapid technological advancements, with e-commerce being one of the most prominent innovations that caters to people's needs and saves time. In this study, we examine the factors that significantly influence user satisfaction in Shopee, a popular e-commerce platform, using the End User Computing Satisfaction (EUCS) method. Data was collected through the distribution of questionnaires to students in the DKI Jakarta area. Our analysis revealed that Content, Accuracy, Format, Ease of Use, Timeliness, and Fulfillment are all significant factors that affect user satisfaction. Together, these factors explain 78.7% of user satisfaction. Additionally, through T-tests, we found that only three variables have a significant and positive impact on user satisfaction: Ease of Use, Timeliness, and Fulfillment. These findings indicate that e-commerce platforms should prioritize these factors to enhance user satisfaction.
Keywords: EUCS; User Satisfaction; E-Commerce